2000
DOI: 10.1046/j.1365-2664.2000.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

The spatio‐temporal distribution of a rodent reservoir host of cutaneous leishmaniasis

Abstract: Summary1. The rodent Psammomys obesus is the main reservoir host for Leishmania major, the causative agent of cutaneous leishmaniasis in Tunisia, much of North Africa and mid-western Asia. An understanding of the population dynamics of this rodent is essential to establish a preventive control strategy based on the early prediction of rodent outbreaks. 2. The study of P. obesus dynamics at a regional scale requires index-based sampling. Rodent numbers were monitored twice per year at the beginning and end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
1
18
0
2
Order By: Relevance
“…Cela dénote une remarquable adaptation écologique chez ce rongeur. Petter rapporte que cette espèce est exclusivement confinée aux réseaux hydrographiques sahariens [23], alors que Fichet-Calvet note que P. obesus peut survivre en dehors de son territoire, notamment en période de stress hydrique, en colonisant des surfaces riches en plantes de la famille des Chénopodiacées, loin des Chotts [13,18]. Cette présence dans le sous-bassin d'El M'hir est liée à des facteurs édaphiques particuliers, notamment la présence de salinité d'origine géologique (marnes gypsosalines).…”
Section: Discussionunclassified
“…Cela dénote une remarquable adaptation écologique chez ce rongeur. Petter rapporte que cette espèce est exclusivement confinée aux réseaux hydrographiques sahariens [23], alors que Fichet-Calvet note que P. obesus peut survivre en dehors de son territoire, notamment en période de stress hydrique, en colonisant des surfaces riches en plantes de la famille des Chénopodiacées, loin des Chotts [13,18]. Cette présence dans le sous-bassin d'El M'hir est liée à des facteurs édaphiques particuliers, notamment la présence de salinité d'origine géologique (marnes gypsosalines).…”
Section: Discussionunclassified
“…The high OR values for the clusters corresponding to pediatric cases located in the southern and eastern areas of the city might be related to increases in periurban reservoirs as a source of parasites and their overlap with vector distribution in borders having transitional landscape of urban-rural or urbanresidual vegetation ( Figure 5 ). 22,43 The association between ACL prevalence and the basic unstatisfied needs index could be related to peripheral location of settlements with impoverished populations, in which geographic proximity to vector exposure is higher. Among those neighborhoods with clusters with radius = 0, these results indicate that those neighborhoods are entities with particular physical, cultural, and/or socioeconomic characteristics that pose a significant risk for infection.…”
Section: Discussionmentioning
confidence: 99%
“…This vector frequently used rodents' burrows for daytime resting and breeding (Helal et al 1987, Esseghir et al 1993. Many ecological studies of the reservoir hosts identified three rodent species carrying L. major: Psammomys obesus Cretzschmar 1828 with a major part in amplifying the transmission, Meriones shawi Duvernoy 1842 and Meriones libycus Lichtenstein 1823 with a role to propagate the parasite between P. obesus colonies because of their common migration, thus increasing the distribution of the parasite (Bouratbine Balma 1988, Fichet-Calvet et al 2000. P. obesus, the fat sand rat, is distributed through the semidesert on the northern fringe of the Sahara, from Mauritania through Morocco, Algeria, Tunisia, Libya, Egypt, Palestine, Jordan, Saudi Arabia, and Syria.…”
Section: Introductionmentioning
confidence: 99%